DAMPAK PERUBAHAN STATUS BADAN USAHA MILIK NEGARA PT TIMAH TBK MENJADI ANAK PERUSAHAAN BADAN USAHA MILIK NEGARA PT INDONESIA ASAHAN ALUMINIUM (PERSERO) TERHADAP KEWENANGAN AUDIT BPK - Ahmad Khalifah Rabbani; Patricia Rinwigati (UNES Law Review, 2023)
In line with the Government's efforts to increase efficiency in the performance of State-Owned Enterprises (BUMN) in each sector, one of the strategies used is to create BUMN Holding, Further, Government Regulation was stipulated concerning Amendments to Government Regulation Number 44 of 2005 concerning Procedures for Participation and Administration of State Capital in State-Owned Enterprises and Limited Liability Companies Number 72 of 2016. One of the implementation of BUMN Holding was carried out in the Mineral and Coal Mining sector resulting in a change in the status of PT Timah Tbk which was originally a state-owned enterprise (BUMN) based on Government Regulation concerning the Transfer of Forms of a State-owned Tin Mining Company to a Limited Liability Company (Persero) Number 3 of 1976 Changed to become a BUMN Subsidiary with the stipulation of Government Regulation Concerning the Addition of the Republic of Indonesia State Equity Participation into the Share Capital of PT Indonesia Asahan Aluminium Company Number 47 of 2017 where PT Indonesia Asahan Aluminium Tbk (Persero) is BUMN Holding. With the change in status from previously a State-Owned Enterprise (BUMN) to a Subsidiary of a State-Owned Enterprise (AP BUMN), it has an impact on the change in the financial status of PT Timah Tbk, which no longer has state shares/capital in it. Whereas based on the changing status of PT Timah Tbk to a BUMN Subsidiary of PT Indonesia Asahan Aluminium (Persero), there is legal dualism related to the authority of the Supreme Audit Agency (BPK) to audit PT Timah Tbk